In silico studying of the whole protein structure and dynamics of Dickkopf family members showed that N-terminal domain of Dickkopf 2 in contrary to other Dickkopfs facilitates its interaction with low density lipoprotein receptor related protein 5/6. Issue 10 (3rd July 2019) - Sadeghi, Solmaz; Poorebrahim, Mansour; Rahimi, Hamzeh; Karimipoor, Morteza; Azadmanesh, Kayhan; Khorramizadeh, Mohammad Reza; Teimoori-Toolabi, Ladan
Abstract: Wnt (Wingless Int) signaling pathway has been known to be dysregulated in several human cancers, especially colorectal cancer (CRC). The Dickkopf (DKK) family which consists of four secreted proteins in vertebrates (DKK 1, 2, 3, 4) is one of the most critical antagonist families for Wnt signaling pathway. They typically antagonize Wnt/β-catenin signaling by binding and inhibiting Wnt co-receptors, LRP5/6 (low density lipoprotein receptor related protein 5/6). However, except for DKK1 (Dickkopf 1), details about structure and function of the members of this family are poorly defined. In this study, main Dickkopf family members were analyzed structurally, using protein structure prediction tools, molecular dynamics (MD), molecular docking and energy analyses. Three dimensional structure of whole DKKs was predicted and their interaction with LRP6 was investigated in detail. The results indicated that in DKK family members, a considerable diversity, in the case of structure, activity and physicochemical properties was seen. This diversity was more profound in DKK3 (Dickkopf3). Interestingly, the interaction mode of DKK2 (Dickkopf2) with its receptor, LRP6, was shown to be substantially different from other Dickkopf family members while N -terminal region of this ligand was also involved in the binding to the LRP6-P3P4. Moreover, the cysteine-rich domain 2 (CRD2) of DKK1 and DKK3 had a higher binding affinity to LRP6 in comparison with the whole protein structures. Communicated by Ramaswamy H. Sarma